The Effect Of Climate Change On Productivity Of Clove (Syzigium Aromaticum) In Haruku Island, Central Maluk Regency - Imelda Jeanette Lawalata; Herman Rehatta; Semuel Leimaheriwa; Johana Audrey Leatemia (Faculty of Agriculture, Pattimura University, 2023)
The world trade history has recorded Maluku as a spice-producing region, including cloves. This commodity has high economic value and is the main source of income for farmers in several areas in Maluku Province. Climate is an environmental factor that also influences plant metabolism and physiology, so that changes in some elements of climate can have a negative impact on plant growth and productivity. The objective of this study was to get information regarding effect of climate variable on productivity of cclove in Haruku island, Central Maluku Regency. Data was collected by field srvey, while secondary data was gathered form related agencies. The results showed that the Haruku Island area with a local-unimodal rain pattern experienced an increase in annual rainfall of 11.8% in the period of 1991-2020 compared to the previous period (1961-1990). The rainy season rainfall (April-September) tends to increase by 15.2%, while the dry season rainfall (October-March) does not show a significant increase, namely only 1.3%. In the last 60 years (1961 – 2020) in the Haruku Island region, El-Nino extreme dry rainfall occurred 19 times. La-Nina wet extreme rainfall events occurred 14 times. Climate variables that affect production are the average annual length of solar radiation, the average annual relative humidity and the amount of annual rainfall